Stress analyses of high-rated capacity large diameter offshore wind turbines: Analytical and numerical analyses of uniform corrosion effects - Okenyi, Victor; Bodaghi, Mahdi; Siegkas, Petros; Mansfield, Neil; Afazov, Shukri (My University, 2023)
As the wind energy sector grows, offshore wind turbines (OWTs) have been pushed to have higher power outputs. This has led to large-diameter OWT support structures that are capable of withstanding aerodynamic and hydrodynamic loads as well as corrosion. This research analyses a 15 MW (MW) OWT support structure using analytical and numerical models. The analytical model was applied based on the Euler-Bernoulli beam theory. Static and modal finite element models were also applied. The structural stability implications of uniform corrosion on the stress evolution of the monopile and tower at different corrosion zones were discussed. Analytical and numerical (finite element analysis) predictions of stress evolution for different wind velocities and uniform corrosion material loss showed an agreement. The analyses showed that material loss due to corrosion increased the stress levels in the support structure. The location of the maximum tensile stress changed from the submerged to the splash zone, indicating that the splash zone may accumulate more damage over time due to the reduction of the monopile thickness and generation of local pits. Predicting the stress evolution due to uniform corrosion could be instrumental in the future designs of OWTs. It can be integral to fatigue assessments for enabling more detailed and accurate life predictions.
Keywords: Offshore wind turbine; Uniform corrosion; Monopile; Finite element analysis; Stress analysis; Structural integrity